Effects of elexacaftor/tezacaftor/ivacaftor therapy on mental health of patients with cystic fibrosis - Piehler, Linus; Thalemann, Ralf; Lehmann, Christine; Thee, Stephanie; Röhmel, Jobst; Syunyaeva, Zulfiya; Stahl, Mirjam; Mall, Marcus A.; Graeber, Simon Y. (Frontiers in Pharmacology, 2023)
Introduction: The CFTR modulator drug elexacaftor/tezacaftor/ivacaftor (ETI) was shown to improve CFTR function and clinical symptoms in patients with cystic fibrosis (CF) with at least one F508del allele. Recently, some case reports suggested potential side effects of ETI on mental health with an increase in depressive symptoms and even suicide attempts in patients with CF. However, the general effects of this triple combination therapy on the mental health status of patients with CF remain largely unknown. Methods: We, therefore, performed a prospective, observational study in a real-life setting and investigated the relationship between initiation of ETI therapy and changes in mental health in adult patients with CF. We assessed Cystic Fibrosis Questionnaire-Revised (CFQ-R), Patient Health Questionnaire-9 (PHQ-9), Beck’s Depression Inventory – Fast Screen (BDI-FS) and Generalized Anxiety Disorder 7-item Scale (GAD-7) at baseline and 8-16 weeks after initiation of ETI. Results: In total, 70 adult patients with CF with at least one F508del allele and a median age of 27.9 years were recruited. After initiation of ETI, the CFQ-R respiratory domain score improved by 27.9 (IQR 5.6 to 47.2; P < 0.001). The PHQ-9 score of depressive symptoms decreased by 1.0 (IQR -3.0 to 0.3; P < 0.05) with an increase of 16.9% in the group with a minimal score after initiation of ETI and a decrease in the groups of mild (-11.3%) or moderate (-5.7%) scores compared to baseline. The BDI-FS score of depressive symptoms decreased from 1.0 (IQR 0.0 to 2.0) at baseline to 0.0 (IQR 0.0 to 2.0; P < 0.05) after initiation of ETI. The group with a minimal BDI-FS score increased by 8.0% after initiation of ETI, whereas the groups with mild (-4.9%), moderate (-1.6%) or severe (-1.6%) scores decreased compared to baseline. The GAD-7 score of anxiety symptoms did not change after initiation of ETI compared to baseline (0.0; IQR -2.0. to 0.0; P = 0.112). Conclusion: Initiation of ETI improves symptoms of depression in adult patients with CF with at least one F508del allele. However, symptoms of anxiety do not change after short-term therapy with ETI.